Operational efficiency performance modelling of Malaysia manufacturing industry - Abdullah, Fader; Ku-Mahamud, Ku Ruhana; Ismail, Ahmad; Mat Kasim, Maznah (2012)
This paper presents an alternative measurement performance system for public listed manufacturing based industry in Malaysia. An operational efficiency performance model for the production of each company was developed using the non-parametric approach, specifically the data envelopment analysis. The performance has been measured through the use of output-oriented based on CCR and BCC models.Data from 80 consumer and industrial product companies were used. The data consists of six inputs and two outputs obtained from financial statement for the year 2010.Experimental result was able to identify efficient and inefficient companies where half of the companies were considered almost efficient under the BCC model. However, only one third of the companies were near efficient when out orientation is performed under the CCR model.